Pesquisa participante: metodologia pedagógica alternativa para enfermeiros - Madeira, Lélia Maria (1985)
In this paper made up with a group of nurses from a governamental school hospital, the methodology used was that of the participating research, taking the praxis philosophy as a theoretic reference. The children hospitalization problem was discussed in the group throughout . the principies of the dcmocracy emphasising the admission. But other necessities and priorities arouse using the historical dialectical approaching. They will be studied continually.The critical analysis of the problem showed us that the nurses made a great progress , individually or as a group, in their view of the reality. They gained a more reflexive and criticai class conscience despite until begining.